2019
DOI: 10.1103/physrevb.99.180302
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of transport in nondisordered quantum spin chains due to confined excitations

Abstract: The laws of thermodynamics require any initial macroscopic inhomogeneity in extended manybody systems to be smoothed out by the time evolution through the activation of transport processes. In generic, non-integrable quantum systems, transport is expected to be governed by a diffusion law, whereas a sufficiently strong quenched disorder can suppress it completely due to many-body localization of quantum excitations. Here we show that the confinement of quasi-particles can also lead to transport suppression eve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 106 publications
11
85
0
Order By: Relevance
“…When presenting our results in the next section, we compare them to the prior work in detail. We remark that inhomogeneous quenches in one-dimensional systems are being addressed in a wider context of interacting integrable models such as the XXZ chain [42,43] (the result of the latter reference for the Loschmidt echo is consistent with our result in the appropriate limit) and nonintegrable models such as the interacting resonant level model [44][45][46][47], nonintegrable Ising spin chain [48] and various models of the molecular and superconducting junctions [49][50][51][52].…”
supporting
confidence: 82%
“…When presenting our results in the next section, we compare them to the prior work in detail. We remark that inhomogeneous quenches in one-dimensional systems are being addressed in a wider context of interacting integrable models such as the XXZ chain [42,43] (the result of the latter reference for the Loschmidt echo is consistent with our result in the appropriate limit) and nonintegrable models such as the interacting resonant level model [44][45][46][47], nonintegrable Ising spin chain [48] and various models of the molecular and superconducting junctions [49][50][51][52].…”
supporting
confidence: 82%
“…This movitates us to study thermalization in our long-range model. Previous studies of the short-range Ising model have observed rapid (strong) or slow (weak) thermalization of one-point functions for different initial states [41,42,48,49,[73][74][75][76]. As first shown in Ref.…”
mentioning
confidence: 63%
“…The lattice model (33) has been investigated extensively, with the quench dynamics receiving particular attention. 25,102,[109][110][111][112][113][114] Bañuls et al 109 showed that certain initial states do not appear to thermalize, in spite of the lack of integrability. It is thought that this is linked to the presence of rare states in the spectrum.…”
Section: Our Lattice Hamiltonian Readsmentioning
confidence: 99%